Political networks and social movements : Bolivian state-society relations under Evo Morales, 2006-2016 - Valdivia Rivera, Soledad (Latin America studies, 2019)
After a landslide electoral victory in 2006, Evo Morales became the first Indigenous President of Bolivia. Morales's stunning ascent was mirrored by the rising fortunes of his political party, the leftist Movimiento al Socialismo, which today continues to challenge the status quo in Bolivian politics and implement ambitious social reforms. This study examines how the state and social movements have impacted democratization in Bolivia, along with other sectors such as NGOs and the media. Soledad Valdivia Rivera's analysis helps us to understand how the movement's relationships have come to transform the Bolivian political process as we know it.